128 Development of an M1-polarized, non-viral chimeric antigen receptor macrophage (CAR-M) platform for cancer immunotherapy. (9th November 2020) - Ohtani, Yumi; Ross, Kayleigh; Dandekar, Aditya; Gabbasov, Rashid; Klichinsky, Michael
Abstract : Background: We have previously developed CAR-M as a novel cell therapy approach for the treatment of solid tumors. 1 CAR-M have the potential to overcome key challenges that cell therapies face in the solid tumor setting – tumor infiltration, immunosuppression, lymphocyte exclusion – and can induce epitope spreading to overcome target antigen heterogeneity. While macrophages transduced with the adenoviral vector Ad5f35 (Ad CAR-M) traffic to tumors, provide robust anti-tumor activity, and recruit and activate T cells, we sought to identify a robust non-viral method of macrophage engineering in order to reduce the cost of goods, manufacturing complexity, and potential immunogenicity associated with viral vectors. Methods: As innate immune cells, macrophages detect exogenous nucleic acids and respond with inflammatory and apoptotic programs. Thus, we sought to identify a means of mRNA delivery that avoids recognition by innate immune sensors. We screened a broad panel of mRNA encoding an anti-HER2 CAR comprising multiplexed 5'Cap and base modifications using an optimized and scalable electroporation approach and evaluated the impact of interferon-β priming on CAR-M phenotype and function. Results: We identified the optimal multiplexed mRNA modifications that led to maximal macrophage viability, transfection efficiency, intensity of CAR expression, and duration of expression. Non-viral HER2 CAR-M phagocytosed and killed human HER2+ tumor cells. Unlike Ad CAR-M, mRNA CAR-M were not skewed toward an M1 state by mRNA electroporation. Priming non-viral CAR-M with IFN-β induced a durable M1 phenotype, as shown by stable upregulation of numerous M1 markers and pathways. IFN-β priming significantly enhanced the anti-tumor activity of CAR but not control macrophages. IFN-β primed mRNA CAR-M were resistant to M2 conversion, maintaining an M1 phenotype despite challenge with various immunosuppressive factors, and converted bystander M2 macrophages toward M1. Interestingly, priming mRNA CAR-M with IFN-β significantly enhanced the persistence of CAR expression, overcoming the known issue of rapid mRNA turnover. RNA-seq analysis revealed that IFN-β priming affected pathways involved in increasing translation and decreasing RNA degradation in human macrophages. Conclusions: We have established a novel, optimized non-viral CAR-M platform based on chemically modified mRNA and IFN-β priming. IFN-β priming induced a durable M1 phenotype, improved CAR expression, improved CAR persistence, led to enhanced anti-tumor function, and rendered resistance to immunosuppressive factors. This novel platform is amenable to scale-up, GMP manufacturing, and represents an advance in the development of CAR-M. Reference: Klichinsky M, Ruella M, Shestova O, et al. Human chimeric antigen receptor macrophages for cancer immunotherapy. Nat Biotechnol 2020;38(8):947–953.